Familial adenomatous polyposis in an adolescent with coexisting schizophrenia: treatment strategies and implications. Issue 5 (3rd December 2014) - Gonzalez, Luisa; Alvarez, Jose; Weinstein, Erica; Korenis, Panagiota
Abstract: Schizophrenia is associated with high mortality and morbidity. The etiology of schizophrenia remains unclear, studies implicate a multifactorial origin with genetic and environmental factors. The adenomatous polyposis coli (APC) gene has been associated with FAP (familial adenomatous polyposis), and studies have linked it to schizophrenia. However, there are few studies which examine the association between FAP and schizophrenia. Limited data exist regarding recommendations for genetic counseling of adolescents with comorbid psychiatric illness. A case of an adolescent with FAP who developed psychotic symptoms is presented. This case hopes to add to the literature about mental illness in those with FAP. A review of literature about the role of APC in schizophrenia as well as implications of genetic counseling on those who suffer with mental illness will be discussed. Abstract : The etiology of schizophrenia remains unclear, twin and adoption studies implicate a multifactorial origin with genetic factors playing a more dominant role than environmental factors. One gene associated with schizophrenia has been the adenomatous polyposis coli (APC) gene; a tumor suppressor gene that increases one's risk for cancer, specifically, colorectal cancer and familial adenomatous polyposis (FAP). Studies have shown that FAP in one family member may lead to a high level of mental health problems in other members of the family, particularly adolescents including: oppositional defiant disorder, adjustment disorder, major depression and anxiety disorder. However, there are few studies which examine the 4 potential association between FAP and schizophrenia.